2012
DOI: 10.1007/s10238-012-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced CD19 expression and decreased memory B cell numbers in transient hypogammaglobulinemia of infancy

Abstract: We aimed to evaluate the role of the CD19 complex in the pathogenesis of transient hypogammaglobulinemia of infancy (THI) and to better characterize the subsets of memory B cells. The study population consisted of 22 male and 14 female patients with a mean age at presentation of 20 ± 9.9 months. The CD19 complex and B cell subsets were evaluated by flow cytometry. While the CD19 median fluorescence index (MFI) in patients with THI was significantly lower than controls (122.9 ± 66.7 in patients; 184.2 ± 39 in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…2,14,22,23 Similarly, we had found both the initial lymphocyte subset percentages and their absolute counts to be in the normal range in our present and in our previous studies 9 . In the report by Artac et al, 24 T-cell, B-cell and NK-cell counts were also within normal ranges. Percentages of CD19 in B cells were normal, but CD19 median fluorescence intensity was lower in THI patients than in the control group.…”
Section: Discussionmentioning
confidence: 72%
“…2,14,22,23 Similarly, we had found both the initial lymphocyte subset percentages and their absolute counts to be in the normal range in our present and in our previous studies 9 . In the report by Artac et al, 24 T-cell, B-cell and NK-cell counts were also within normal ranges. Percentages of CD19 in B cells were normal, but CD19 median fluorescence intensity was lower in THI patients than in the control group.…”
Section: Discussionmentioning
confidence: 72%
“…The authors found low intensity of CD19 expression, which they suggested could interfere with B cell activation, leading to diminished immunoglobulin production. 22 In contrast, Bukowska-Strakova et al evaluated the B cells of children with THI compared to normal control subjects. There were no differences between children with THI and control subjects of similar age.…”
Section: B Cell Abnormalitiesmentioning
confidence: 92%
“…Reviews of published series of infants and children diagnosed as having THI show relatively mild recurrent otitis media and upper respiratory infections to be the primary reason that immunoglobulin levels were determined. More serious infections are reported in some of these children, including pneumonia, 6,10,14 sepsis, 6,10,19,22 meningitis, 10,15,22 recurrent gastroenteritis, 10,14,22,24,25,29 recurrent urinary tract infections, 8,18,22,24 vaccine associated polio meningoencephalitis, 43 and deep tissue infections. 14,44 Opportunistic infections, including Pneumocystis jirovecii pneumonia 45 and chronic candidiasis, are also reported.…”
Section: Clinical Presentationmentioning
confidence: 96%
See 2 more Smart Citations